Bilangan Dominasi-Lokasi pada Graf Hasil Kali Operasi Comb Graf Lintasan dan Graf Siklus - Aswan Anggun Pribadi; Muhammad Dhani; Anastasia Lia Dwi Prestanti (Indonesian Journal of Applied Mathematics, 2023)
Dominating set of graph G is subset D⊆V(G) which for every vertex v∈V(G)\D those vertices has neighbour in D. If for every pairs of vertice x and y their neighbour set different than we called D locating-dominating set. As for the minimum cardinality of possible dominating set of G is called the locating-dominating number of G. We determine the value of the locating-dominating number for comb product path (Pn) and cycle (Cn) graph.